Mr. Schweinfurth correspondence - Schweinfurth, Mr.
Letter written by Schweinfurth of Karlsruhe, Germany, in reply to a letter from a Mr. Schlevitz.
Collection material in German.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Schlevitz, -- Mr. -- Correspondence; Germany -- Social life and customs; Karlsruhe (Germany)